ABSENTEÍSMO POR DOENÇA EM TRABALHADORES DE SAÚDE EM UM HOSPITAL PÚBLICO DO ESTADO DA BAHIA, 2005-2006 - Martins, Patricia Fritas (2008)
The health workers who act in the assistance to the health are displayed to the risk of adducers, in function of the extensive work, hours of working in regimen of plantain, nocturnal work, physical and emotional overload and specificities of the work in health as, to attend the suffering, the illness and the death daily. This work had as objective to know the absenteeism for illness in workers of health of a Public Hospital of the State of the Bahia. So, a descriptive, exploring and epidemiological study was done, considering health workers on sick leave, as the object of study, as well as the medical certificates from the Personal Department at a public hospital of the State of Bahia from July 1st, 2005 to June 30th, 2006. The collection occurred in the March months the August of 2006, being carried through in the Sector of Staff through the folders registers in cadastre of the workers, the certified doctors and document of the Secretariat of Health of the State of the Bahia. For the collection, some forms, with distinct variables, were filled out: the principal form absence for sickness ( time of absence and disease); the social demographic form ( age, sex, married status, number of children s) and the characteristics of work form ( profession, department, type of contract, weekly work hours, time of work at the hospital). At first, it was observed that health workers on sick leave completed a mean of 2,31% of medical certificates, and it was also observed that 31,9% (267) of professionals got sick during the studied period, which represented a high index of illness. The results pointed out that health workers on sick leave were predominantly women, with the age of 40 (forty) or superior to it. It also pointed out that those people have worked at the hospital for 12, 5 years or more. Most types of workers had a statutary contract with 40 (forty) hours per week. Among the work departments, UTI Unidade de Terapia Intensiva (Intensive Therapy Unit), and First-aid station were stood out, and among the workers, most on sick leave were nurses. The average time on sick leave was 4.5 within 4.4 days. Respiratory and musculoskeletal diseases were most common, followed by factors that have influenced health and the contact with health services. This work can begin new dialogues on characteristics affect the workers health. We hope the results from study can stimulate the creation and implementation of a Serviço de Atendimento à Saúde do Trabalhador (an Organ which can take care of health workers).